Assessment of the neuromuscular characteristics of the flexo-extension muscles of knee by tensiomyography in elite soccer players: a systematic review - Lorigados Pérez, J.; Bustamante-Sánchez, Á. (Frontiers in Sports and Active Living, 2025)
Introduction: The objective was to summarize the usefulness of tensiomyography (TMG) as a monitoring tool to evaluate the neuromuscular characteristics of the knee flexor and extensor muscles in elite male soccer players.